THE EFFECT OF ADDITION Spirulina TO THE CATFISH (Pangasius hypophthalmus) FISH PROTEIN CONCENTRATE ICE CREAM ON THE CONSUMER ACCEPTANCE - Trisna Wiga Putri; N. Ira Sari; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aimed To determine the optimum quality of Spirulina added to the catfish (Pangasius hypophthalmus) PFC ice cream making accepted by consumers. The method used was experimental and composed as CDR. The treatment consisted of 4 levels, namely: S0 (without Spirulina, as a control), S1 (0,45% Spirulina), S2 (0,60% Spirulina), and S3 (0,75% Spirulina). The parameters used were chemical and organoleptic evaluation. The result showed that the FPC ice cream added with Spirulina 3,6 g was indicated the highest consumer acceptance at 90%. The characteristic of appearance was green, little smell of Spirulina, the texture was soft and the flavor was sweet and delicious. The product contained 48,18% water, 19,46% protein, 3,19% fat and characterized emulsion stability 88,56%.Keywords : Ice cream, Fish Pritein Concentrate, Spirulina.